SYNTAX IN SERBIAN LANGUAGE TEACHING IN THE SECOND CYCLE OF COMPULSORY EDUCATION (Heritage, 2020)
The aims, tasks and outcomes of teaching the subjects of the Serbian language and Serbian language and literature in the second cycle of compulsory education are aimed at developing the competence of the student's personality that will master the correct use of the Serbian language in written and spoken communication. The National Education Council has prescribed Standards that are a measure of the achievement of the planned educational goals. Textbooks that can be used in teaching Serbian are approved by the Institute for the Advancement of Education and meet the prescribed standards for textbook quality.The content of the textbooks that we have insight into is aligned with the curriculum, contributes to meeting the prescribed standards, the contents are based on accepted scientific theories, facts and conclusions, the visual contents are clear and have different functions, are aligned with the value system defined by the educational goals and upbringing, they connect the contents within the same subject between classes. Reforms of teaching aimed at achieving learning outcomes also bring new ways of monitoring and evaluating student achievement (formative assessment), compulsory project teaching, and innovations in teacher planning.
Keywords: Objective, tasks, operational tasks, teaching contents, outcomes, standards, Serbian language, syntax